Closer view of the elevation of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
Closer view of the elevation of the garbhagriha (sanctum sanctorum) of the Bhandasar Temple. The two projections visible in the picture, show few basal mouldings of the plinth are covered in the later added flooring. From the remaining portions, from bottom to top, the mouldings are kumbha (pot), kalasha (a pitcher) and kapotali (cyma recta) of the vedibandha (basal mouldings). This is followed by the jangha (wall) that further connects to the cornice of the temple.